Simplifying The Blue Economy for Msmes in the Riverbank and Coastal Areas of Kerobokan, Buleleng: A Sustainable Approach to Community Empowerment - Komang Adi Kurniawan SAPUTRA; Putu Ayu Sita LAKSMI; I Wayan Werasmana SANCAYA; Made Adinda Anugrah Deva PRAMAISWARI; I Gede Candra Adi PRATIKA (PT Keberlanjutan Strategis Indonesia, 2025)
This community service program aims to empower MSMEs in the riverbank and coastal areas of Kerobokan, Buleleng, through the application of a simplified blue economy concept. The program was implemented for 8 months and involved 20 MSMEs from the